THE EFFECTIVENESS OF JCONNECT SIPANDAI IN IMPROVING SERVICE QUALITY IN TAX PAYMENTS AT BUMDES TRI KARYA AGUNG IN KEBONAGUNG VILLAGE - Azzahra, Adelia Annisa Rahmania; Choiriyah, Ilmi Usrotin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the obstacles faced by BUMDes Kebonagung in providing Motor Vehicle Tax (PKB) and Land and Building Tax (PBB) payment services through the JConnect SiPandai application developed by Bank Jatim, with a focus on system quality, information quality, and user satisfaction. Method: A qualitative case study was conducted from January to March 2025 using in-depth interviews with the BUMDes Director, direct observations, and analysis based on the DeLone & McLean information system success model. Results: The findings indicate that the system quality still encounters technical challenges, including login failures during peak hours, limited integration with external parties, and exclusive smartphone-based access. Nevertheless, the information quality was perceived as accurate, relevant, and real-time, thereby supporting tax management. Although user satisfaction decreased due to technical barriers, the active role of BUMDes as facilitators helped maintain service accessibility. Novelty: This study contributes new insights into village-based digital tax services by highlighting the critical interplay between system reliability, information quality, and institutional support, an area that has rarely been examined in prior research on local-level digital governance.